2020
DOI: 10.1007/s40732-020-00393-3
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Stimulus Control and Conditioned Reinforcement

Abstract: Stimuli with no specific biological relevance for the organism can acquire multiple functions through conditioning procedures. Conditioning procedures involving compound stimuli sometimes result in blocking, related to the phenomenon of overshadowing. This can affect the establishment of conditioned stimuli in classical conditioning and discriminative stimuli in operant conditioning. The aim of the current experiment was to investigate whether a standard blocking procedure might block the establishment of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Replication of the stimulus control test showed the same consistent result: The S 1 + , which was established during the first phase of the discrimination training, was still effective, whereas S 2 + , which was added during the second phase, was not. The results of the present study are in accord with the results of previous studies that have demonstrated blocking of discriminative control in animals (e.g., Vandbakk et al, 2020;vom Saal & Jenkins, 1970) and in humans. However, results of previous experiments with humans have varied, and so have the procedures used in those experiments.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Replication of the stimulus control test showed the same consistent result: The S 1 + , which was established during the first phase of the discrimination training, was still effective, whereas S 2 + , which was added during the second phase, was not. The results of the present study are in accord with the results of previous studies that have demonstrated blocking of discriminative control in animals (e.g., Vandbakk et al, 2020;vom Saal & Jenkins, 1970) and in humans. However, results of previous experiments with humans have varied, and so have the procedures used in those experiments.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the added stimulus did not show reinforcing properties when contingent upon a novel response. Thus, Vandbakk et al (2020) supported previous research on the blocking effect in animals using an operant discrimination training procedure.…”
supporting
confidence: 86%
See 3 more Smart Citations